Some Properties of the -Extension of the -Adic Gamma Function - Hamza Menken; Adviye Körükçü (Abstract and Applied Analysis)
We study the -extension of the -adic gamma function . We give a new identity for the -extension of the -adic gamma in the case . Also, we derive some properties and new representations of the -extension of the -adic gamma in general case.